Pagkatao, pagkababae at pagkalalaki (how prostituted children view themselves, their sexuality and their experience of prostitution - Arellano-Carandang, Ma. Lourdes; Fernando, Priscilla G.; Sison, Beatrix Aileen L. (1999)
This is a phenomenological study on the sexuality and self-concept of boys and girls in prostitution. Twelve boys and 12 girls, ages 11 to 17, were selected on the basis of the having been in prostitution for at least one year. In-depth clinical interviews, projective tests, and a clinical assessment package were administered by a team o trained and experienced research-therapists. Counseling sessions were held when necessary to make sure that re-opened wounds were handled properly. The responses were analyzed using a modified interrater clinical judgment and discussion-consensus model. The results showed interesting differences in the views and inner dynamics between the boys and the girls. For example, while both indicated some kind of "split" or dissociative process, the girls' self concept issues had to do with being "defiled", dehumanized, and "damaged", while the boys were not concerned about being "damaged" but were fearful of becoming homosexual. These and other findings are discussed in the cultural context of the larger Filipino society. Finally, different intervention strategies for boys and girls are discussed.
Includes bibliographical references (pages 112-113).